Applications on the Closed Ideals in the Big Lipschitz Algebras of Series of Analytic Functions - Musa Siddig; Shawgy Hussein; Abdelrehaman Mohamed (European Journal of Scientific Exploration, 2021)
We show an applications the closed ideals in the big Lipschitz algebras of series of analytic functions on the unit disk of closedness distinct elements. We give the smallest closed ideal with given hull and inner factor.